2010
DOI: 10.1177/1059840510366022
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Planned Behavior to Predict Mothers’ Intentions to Vaccinate Their Daughters Against HPV

Abstract: This study assessed mothers' intentions to vaccinate their daughters against human papillomavirus (HPV) using the theory of planned behavior (TPB). Experience with sexually transmitted infections (STIs), beliefs about the vaccine encouraging sexual activity, and perception of daughters' risk for HPV were also examined for a relationship with intention. A random sample of mothers in a rural, Midwestern state were mailed a survey with questions pertaining to the intention to vaccinate. Attitudes were the stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 31 publications
9
97
2
2
Order By: Relevance
“…This may be due to the fact that most respondents in our study perceived that their daughters or girls under supervision were at low risk for genital warts and that genital wart is not a severe disease. Consistent with previous studies (Askelson et al, 2010;Ferris et al, 2010;Juraskova et al, 2011), the perception that the vaccine would encourage inappropriate sexual behavior was unlikely to be a barrier of acceptance while concerning about safety of vaccine was identified as the important reason for non-acceptance among Thai parents (National Cancer Institute 2011;Ortashi et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This may be due to the fact that most respondents in our study perceived that their daughters or girls under supervision were at low risk for genital warts and that genital wart is not a severe disease. Consistent with previous studies (Askelson et al, 2010;Ferris et al, 2010;Juraskova et al, 2011), the perception that the vaccine would encourage inappropriate sexual behavior was unlikely to be a barrier of acceptance while concerning about safety of vaccine was identified as the important reason for non-acceptance among Thai parents (National Cancer Institute 2011;Ortashi et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…According to the previous studies, many parents, providers and girls indicated that they would wait until the girls were older to get vaccinated (Askelson et al, 2010;Paul-Ebhohimhen et al, 2010;Rose et al, 2010;Hanley et al, 2012;Pitts and Adams, 2013;Madhivanan et al, 2014). Since Thai teens begin to have sex at an early age, and because Thai parents are often not really aware of their children's sexual behavior and are less likely to discuss sex with their children (Sridawruang, et al, 2010;Fongkaew et al, 2012), education should emphasize on the fact that it is necessary to be vaccinated against HPV at a young age, especially before the onset of sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…The TPB model predicts that women have higher intentions to utilize cervical cancer prevention measures if they have significant perceived behavioral control (Askelson et al, 2010;Teitelman et al, 2011). Factors affecting perceived control may include accessibility to a family doctor (Bish et al, 2000), time (Markovic et al, 2005), and affordability of Pap smear and vaccination (Menvielle, Richard, Ringa, Dray-Spira, & Beck, 2014;Taylor et al, 2002).…”
Section: Research-article2014mentioning
confidence: 99%
“…Furthermore, it predicts carrying out exercises (Blue, 1995), playing the video games (Doll & Ajzen, 1992) and introducing complementary feeding to infants at six months old (Hamilton, Daniels, White, Murray & Walsh, 2011). Moreover, this theory has been previously used in assessing the attitude of breastfeeding (Giles et al, 2007) and in predicting the mother's intention to vaccinate their daughters (Askelson et al, 2010).…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%